A Case of Sevoflurane Use during Pregnancy in the Management of Persistent Status Asthmaticus - Jessica Parrott; Mitch Tener; Katie Dennis; Matthew Sharpe; Cecily Clark-Ganheart (Case Reports in Obstetrics and Gynecology)
Background. Sevoflurane is rarely used for the treatment of status asthmaticus. We report a case of sevoflurane hepatotoxicity in pregnancy with presentation similar to HELLP syndrome. Case. A G2P1001 at 23 weeks in status asthmaticus presented with pCO2 > 130 and pH < 7. She was nonresponsive to traditional therapy. Sevoflurane was added for a 24 hr period. Respiratory status improved. Extubation occurred on day 12. Workup for preeclampsia spectrum disorders occurred due to maternal hypertension. Given the atypical presentation and hepatotoxicity, a liver biopsy was performed. Histologic features suggested drug induced hepatic injury. Liver function subsequently normalized. She delivered a term neonate without short-term complications. Conclusion. The use of sevoflurane is a treatment option of status asthmaticus during pregnancy. Providers should be aware of the potential for hepatotoxicity.